Validating the “Two Faces” of Envy: The Effect of Self-Control - Yang, Chen; Tang, Rixin (Frontiers in Psychology, 2021)
Envy drives different behaviors, and while we often emphasize the negative effects of envy, there are also relatively positive aspects. In two experiments, this study explored the “two faces” of envy or behavior that elevates oneself or degrades others. In Experiment 1, we modeled the effects of envy and self-control on effort and aggression. In Experiment 2, we explored the influence of envy on striving behavior and aggressive behavior in different ego depletion states. The different effects of envy on different levels were doubly verified. Results showed that: (1) The structural equation models of self-control, benign envy, malicious envy, and their different behaviors are established; (2) Individuals’ striving behavior was only affected by benign envy; (3) Individuals’ aggressive behavior was influenced by both malicious envy and self-control. Ego depletion moderated the effect of malicious envy on aggressive behavior.